Synthesis of Nanosized Zeolite Catalyst Particles from Waste Materials for Efficient Removal of Fe(III) from aqueous solution - Smail, Heman A. (Sulaimani Journal for Pure and Applied Sciences, 2023)
The objective of this study was to prepare zeolite ZSM-5 nanostructure from aluminum foil drug sachet waste by a simple conventional hydrothermal method using different times (24, 48, 72, and 96 h), and to figure out the adsorption capacity of zeolite ZSM-5 nanostructure for heavy metal of Fe(III) . The best time for synthesizing and testing the adsorption effectiveness of the provided ZSM-5 zeolite is 96 h. The ZSM-5 zeolite is defined by X-ray diffraction (XRD), Brunauer Emmett Teller (BET), Field Emission Scanning Electron Microscopy (FESEM) and Fourier transform infrared spectroscopy (FTIR) for confirming their structure and properties, such as crystal structure, surface area, and surface morphology. The crystallinity percentage of nanosized ZSM-5 was 100%, and the surface area and micropore volume were 368.70 m2 /g and 0.158 cm3 /g, respectively. In addition, the ZSM-5's adsorption efficiency the solution for Fe(III) was tested. Many factors, including adsorption properties, contact duration, initial iron solution content, and pH, were investigated. The equilibrium was reached after 25 minutes. pH levels between 3.0 and 4.0 were shown to be optimal for the absorption of iron solution. The iron species` adsorption capacities in solutions at 298 K were 56.49 mg/g, at 308 K, 86.20 mg/g, and at 318 K, 68.02 mg/g. The findings of the Freundlich adsorptions and Langmuir were used to represent the isotherm constants. The Langmuir model can adequately describe the Fe(III) solutions` adsorption isotherm data while testing at 298K and 308K, whereas those of Fe(III) testing at 308K and 318K were more closely connected to the Freundlich model.
Keywords: ZSM5 zeolite; nanocrystals; aluminumfoil drug sachet waste; adsorption; iron